The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5194/cp-15-539-2019
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity of alkenone carbon isotopes to atmospheric CO<sub>2</sub> at low to moderate CO<sub>2</sub> levels

Abstract: Abstract. Atmospheric pCO2 is a critical component of the global carbon system and is considered to be the major control of Earth's past, present, and future climate. Accurate and precise reconstructions of its concentration through geological time are therefore crucial to our understanding of the Earth system. Ice core records document pCO2 for the past 800 kyr, but at no point during this interval were CO2 levels higher than today. Interpretation of older pCO2 has been hampered by discrepancies during some t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 65 publications
6
52
0
Order By: Relevance
“…There are several possible explanations as to why there is an underestimation. As discussed above, carbonate concentration mechanisms may be operating in a large number of phytoplankton, such that they become relatively enriched in 13 C and thus lead to lower reconstructed pCO 2 values (Stoll et al, 2019;Badger et al, 2019). There is also a large uncertainty in the b value applied, which may be much lower than the value assumed here.…”
Section: Pco 2 Reconstructed From General Algal Biomarkersmentioning
confidence: 78%
See 1 more Smart Citation
“…There are several possible explanations as to why there is an underestimation. As discussed above, carbonate concentration mechanisms may be operating in a large number of phytoplankton, such that they become relatively enriched in 13 C and thus lead to lower reconstructed pCO 2 values (Stoll et al, 2019;Badger et al, 2019). There is also a large uncertainty in the b value applied, which may be much lower than the value assumed here.…”
Section: Pco 2 Reconstructed From General Algal Biomarkersmentioning
confidence: 78%
“…The most studied biomarkers for calculating ε p are alkenones, i.e., long-chain unsaturated methyl and ethyl ketones produced by select haptophytes (Volkman et al, 1980;de Leeuw et al, 1980). The stable carbon isotopic fractionation of alkenones has been studied using cultures and mesocosms with controlled environments (Laws et al, 1995;Benthien et al, 2007), but conditions do not always mimic natural environments and the natural variation in carbonate chemistry that occurs on a daily to seasonal timescales. Furthermore, these experiments are also time-consuming given that they must have delicately balanced water chemistry, including CO 2[aq] concentrations, pH, and alkalinity, as well as nutrients such as nitrate and phosphate (Popp et al, 1998;Laws et al, 1995;Bidigare et al, 1997), along with the additional challenge of maintaining a constant δ 13 C of the CO 2[aq] , while photoautotrophs continually enrich the growth water as they fix CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric CO2 concentration was set at 400 ppmv (Haywood et al, submitted), in line with the upper estimates of atmospheric CO2 from boron isotope data (Figure 1; Foster et al, 2017). Lower estimates from the alkenone carbon isotope proxy ( Figure 1) are likely to reflect an insensitivity of this proxy to atmospheric CO2 in the Pliocene (Badger et al, 2019). All other trace gases, orbital parameters and the solar constant were specified to be consistent with each model's preindustrial experiment.…”
Section: Climate Modelsmentioning
confidence: 99%
“…These biomarkers are almost exclusively alkenones, long-chain unsaturated methyl and ethyl n-ketones produced by haptophytes 8,28,29 . Although this proxy has generated a large number of pCO 2 records [30][31][32] , there are several limitations, such as the exceptionally low Ɛ f recorded for the alkenone-producer Emiliania huxleyi of 11‰ 20 , a potential insensitivity of this proxy at low CO 2 levels 24,33 , and difficulties in constraining the b factor over time 34 . One other limitation is the fact that alkenones first commonly appeared in the geologic record ca.…”
mentioning
confidence: 99%
“…This effect has also been observed in the mesocosm experiments with different CO 2 concentrations 40 , especially if there is limited carbon dioxide leakage from cells. Recent studies have shown lower sensitivity of Ɛ p to CO 2 in laboratory cultures and in glacialinterglacial reconstructions caused by the upregulation of phytoplankton CCMs 24,33 , which suggest using this Ɛ p based proxy with caution in reconstructing low-CO 2 worlds. In contrast, the proxy seems to do well in estimating pCO 2 concentrations similar to some of the higher concentrations that have been reconstructed over the past 455 Myr 39 , suggesting it may be applicable for past greenhouse worlds.…”
mentioning
confidence: 99%